EMPA methods for volcanic glass. v1 ... - Straub, Susanne; Reilly, Brendan; Raymo, Maureen; Gómez-Tuena , Arturo; Wang, Kuo-Lung; Widom, Elisabeth; Kuentz, David; Arculus, Richard (Interdisciplinary Earth Data Alliance (IEDA), 2024)
EMPA methods for volcanic glass using Cameca SXFive Tactics microprobe analyzer equipped with five wavelength dispersive spectrometers at the American Museum of Natural History. ... : Straub, S.M., Reilly, B.T., Raymo, M.E., Gomez Tuena, A., Wang, K.L., Widom, E., Kuentz, D., Arculus, R.J., 2024. Patterns of Plio-Pleistocene Ice Volume Variability Recorded by the Large-Magnitude Explosive Eruptions from the Kamchatka-Kurile Volcanic Arc. Geochem Geophys Geosys, 25. ...